Circular : Basque Children's Trust - Arne, Betty L.
1938-07 038-0126-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: MISS BETTY L. ARNE, BARRISTER-AT-LAW 4, GREAT SMITH STREET, LONDON, S.W.1. TELEPHONE: ABBEY 2565 July, 1938. Dear Sir or Madam, BASQUE CHILDREN'S TRUST. As you will remember, the above private Company has been formed so that any future leases and other legal obligations, hitherto entered into by the officers, may be taken over by the Trust. The Company is a small private one, the number of shares being limited to a total value of £ 50. In order, however, to give confidence to members of the public who may search the Registrar General's files, it is necessary that some individuals in addition to the Directors should take shares in the Company. I enclose an official form herewith and shall be grateful, if you are prepared to support the Basque Children's Trust to the extent of 10/-, if you will fill up the enclosed form and send me the amount as quickly as possible. Your liability, under the Companies Act, is limited to 10/-, the amount of your share. Hoping to hear from you as quickly as possible. Yours sincerely, BETTY L. ARNE Secretary. 292/946/38/126(I)